Improved thermoelectric properties of C-doped Bi2Te3 films following short-range atomic diffusion induced by pulsed electric field treatment. Issue 18 (15th September 2022) - Lan, Mingdi; Sun, Shang; Liu, Shiying; Li, Guojian; Guo, Hailong; Wang, Qiang
Abstract: Bi2 Te3 is a successful and commercial thermoelectric material. However, Bi2 Te3 is easily generates point defects, which limits its thermoelectric (TE) properties. This study presents a novel method to tune point defects by using short-range atomic diffusion via pulsed electric field (PEF) treatment in C-doped Bi2 Te3 films. The C atoms migrate from the interstitial position in the Bi layer (Ci ) and the Van der Waals gap (Cvdw ) to the Bi vacancy after the PEF treatment. For this case, it increases the content of the Te–C bonds for the PEF films, resulting in increased electron concentration. And the PEF can eliminate amorphous regions of the C-doped Bi2 Te3 films. In addition, the shorter bond length of the Te–C improves the compressive stress of the film and increases the effective mass of carriers. Thus, the conductivity and the Seebeck coefficient are improved simultaneously. In this study, the power factor was 2450.32 μW m −1 ·K −2 at 513 K after the PEF treatment. Therefore, the PEF is an effective method to improve TE properties by short-range atomic diffusion.